A multi-physics node-based smoothed radial point interpolation method for transient responses of magneto-electro-elastic structures. (April 2019) - Zhou, Liming; Ren, Shuhui; Meng, Guangwei; Li, Xiaolin; Cheng, Fei
Abstract: A multi-physics node-based smoothed radial point interpolation method (MNS-RPIM) for the transient responses of two-dimensional magneto-electro-elastic (MEE) structures is presented, the displacement, electrical potential and magnetic potential are obtained by combining the coupling MEE Newmark method. Based on constitutive equation of MEE material and introducing the weakened weak (W 2 ) formulation and the G space theory, the discretized system equations are produced. The method developed here is suitable for arbitrary boundary conditions, which could be the complement to the analytical solution. For two-dimensional structures, triangular element is adopted to discrete models because it could be automatically generated for complex geometries. The generalized displacement is computed for a cantilever beam, a layered MEE sensor and a typical MEE energy harvester. Results shows the following important properties of MNS-RPIM: (1) insensitive to mesh distortion; (2) accurate and convergent; (3) volumetric locking free; (4) high efficiency over FEM at the same accuracy.